2022
DOI: 10.1007/s12161-022-02237-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Real-Time PCR Method Claiming to be Specific for Detection and Quantification of the First Commercialised Genome-Edited Plant

Abstract: A real-time PCR method was recently published with a claim to be specific for the detection and identification of some genome-edited oilseed rape (OSR) lines commercialised in North America. The method was designed to detect a single base mutation in the AHAS1C gene, which confers herbicide tolerance. The authors claim that the method is event-specific for the genome-edited OSR line 5715 and fulfils all requirements for GMO analytical methods according to EU regulations. We have thoroughly assessed the method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…As expected, the BLAST analysis of amplicon grf1-3 indicated that the single nucleotide polymorphism was the only difference in 35 sequence hits with 99.8% similarity. Similar results were found by [13] when analyzing amplicons of primer sets for the detection of gene-edited canola. In their study, the BLAST search produced hits in B. oleracea and B. carinata, where the only difference between the targets was the last nucleotide at position 22.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…As expected, the BLAST analysis of amplicon grf1-3 indicated that the single nucleotide polymorphism was the only difference in 35 sequence hits with 99.8% similarity. Similar results were found by [13] when analyzing amplicons of primer sets for the detection of gene-edited canola. In their study, the BLAST search produced hits in B. oleracea and B. carinata, where the only difference between the targets was the last nucleotide at position 22.…”
Section: Discussionsupporting
confidence: 80%
“…The technical complexity of designing a PCR system capable of distinguishing specific sequences with accuracy and reliability requires both in silico and experimental testing. Some studies have successfully distinguished NGT canola and rice varieties using PCR [11,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Several of those already have a GEd regulation in place which allows exemptions of some GEd products from strict GMO regulations including labeling. This situation is contrary to the legislation in Europe, and the situation may worsen, as clear detection and identification of such products in goods is currently not possible without technical details (unique analytical reference data), and will not be possible in the near future ( Grohmann et al, 2019 ; Weidner et al, 2022 ). In the past, many countries remained on hold waiting for Europe to make a move toward a clear regulation (see Sprink et al, 2016 ).…”
Section: Discussionmentioning
confidence: 90%
“…However, while most of the extra-European countries have adopted or are adopting legislations that differentiate many NGT products from GMOs, making their authorization for the market more streamlined and faster, the current European regulatory framework would constitute a strong obstacle to the development of NGTs in Europe [ 214 ]. On a more technical level, the EC identified substantial issues concerning traceability of some products obtained through NGTs because it is possible to analytically detect single-point mutations in a target sequence but not their origin, whether natural or induced in the laboratory [ 215 ]. Therefore, to keep pace with the scientific and technological development and favor European economic and social progress, the EC has decided to test whether the conditions exist in Europe for a change in the legislative framework on NGTs in plants.…”
Section: Regulatory Issues In Europe With a Focus On Italymentioning
confidence: 99%